The selected premises for the reconfiguration of the disability model. The posthumanist perspective - ŻÓŁKOWSKA, TERESA; KALISZEWSKA, KAROLINA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
Teresa Żółkowska, Karolina Kaliszewska, The selected premises for the reconfigura-tion of the disability model. The posthu-manist perspective. Interdisciplinary Contexts of Special Pedagogy, no. 25, Poznań 2019. Pp. 55-81. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2019.25.03 In the contemporary special pedagogy, it is clearly seen, that we are dealing with a situation of passing over scholarly programmes that refer, i.a. to the medical and social model of disability. We remain in a inter-paradigmatic transition period, in which new views on disability are appearing. One of the most popular scholarly approaches is the posthumanism, the characteristics of which are, i.a.: the critique of humanism, the departure from anthropocentrism, the appearance of a new materialism, the direction of research towards objects, animals, as well as, the relations of people and non-people. The example of such posthumanist approach, that may constitute the context for the creation of new models of disability, is the Actor-Network theory developed by Bruno Latour and his associates.